2022
DOI: 10.1149/1945-7111/ac87d2
|View full text |Cite
|
Sign up to set email alerts
|

The Electrolytic Reduction of MoO3 in CaCl2-NaCl Molten Salt

Abstract: Electro-deoxidation reduction technology is a very attractive method used to treat oxides in the metallurgical industry. Here, cyclic voltammetry, square wave voltammetry, and open circuit chronopotentiogram were applied to study the electrochemical behavior of MoO3 cathode in the CaCl2-NaCl melt at 873 K. Through the electrolytic reduction of MoO3 at different potentials (-1.15 V, -1.45 V, and -1.75 V, vs Ag/AgCl) and X-ray diffraction analysis, MoO3 was found to be transformed into several intermediate compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
1
2
0
Order By: Relevance
“…According to the results obtained in Fig. 8 and our previous work of MoO 3 , 23 it could be confirmed that the reduction peak G is MoO 3 → MoO 2 and peak F is MoO 3 → Na 1.4 Mo 2 O 4 . The cathodic peak E corresponded to the reduction of some intermediate products (CaMoO 4 , MoO 2 and Na 1.4 Mo 2 O 4 ) to the metallic Mo.…”
Section: Du Et Al Found That the Electrolytic Reduction Process Of U ...supporting
confidence: 74%
See 1 more Smart Citation
“…According to the results obtained in Fig. 8 and our previous work of MoO 3 , 23 it could be confirmed that the reduction peak G is MoO 3 → MoO 2 and peak F is MoO 3 → Na 1.4 Mo 2 O 4 . The cathodic peak E corresponded to the reduction of some intermediate products (CaMoO 4 , MoO 2 and Na 1.4 Mo 2 O 4 ) to the metallic Mo.…”
Section: Du Et Al Found That the Electrolytic Reduction Process Of U ...supporting
confidence: 74%
“…In our previous studies, cathodic peaks G, F and E should correspond to the generation of MoO 2 , Na 1.4 Mo 2 O 4 and metal Mo, respectively, while the anode peaks F′ at −1.05 V and G′ at −0.33 V (vs Ag/AgCl) belonged to the corresponding oxidation reactions, respectively. 23 Figure 8 showed the XRD patterns of U 3 O 8 and MoO 3 mixture before and after sintering. The U 3 O 8 -MoO 3 tablet was sintered at 923 K for 10 h. Two phases of U 3 O 8 and MoO 3 can be observed in the XRD pattern before sintering.…”
Section: Du Et Al Found That the Electrolytic Reduction Process Of U ...mentioning
confidence: 99%
“…1,4,14 Therefore, the research on developing and optimizing direct reduction of metal oxides technology for metal preparation is essential. At present, many metal oxides, such as TiO 2 , 11,15 ZrO 2 , 16 HfO 2 , 17 Nb 2 O 5 , 18 Ta 2 O 5 , 4 Cr 2 O 3 , 19 MoO 3 , 20 and NiO, 21 etc., have been used as raw materials by this method. Meanwhile, various molten salt systems, such as LiCl, LiCl-Li 2 O, CaCl 2 , CaCl 2 -NaCl, and LiCl-KCl-CaCl 2 , have been used as the electrolytes for the electrolytic reduction process.…”
mentioning
confidence: 99%